Impact of connectivity on the electronic structure of N-heterotriangulenes - Ajdari, Mohsen; Pappenberger, Ronja; Walla, Christian; Hoffmann, Marvin; Michalsky, Ina; Kivala, Milan; Dreuw, Andreas; Tegeder, Petra (The journal of physical chemistry. C, Energy, materials, and catalysis, 2023)
N-heterotriangulenes (N-HTAs) are promising organic semiconductors for applications in field effect transistors and solar cells. Thereby the electronic structure of organic/metal interfaces and thin films is essential for the performance of organic-molecule-based devices. Here, we studied the structural and the electronic properties of two different N-HTAs, N-HTA 550 and N-HTA 557, the latter containing an additional 7-membered ring, adsorbed on Au(111) using vibrational and electronic high-resolution electron energy loss spectroscopy in combination with state-of-the-art quantum chemical calculations. In the mono- and multilayer, both N-HTAs adopt a planar adsorption geometry with the molecular backbone oriented parallel to the gold substrate. The energies of the lowest excited electronic singlet states (S) are assigned. The optical gap (S0 → S1 transition) is found to be 3.4 eV for N-HTA 550 and 2.5 eV for N-HTA 557. Thus, the introduction of the −C═C- double bond in N-HTA 557 resulted in a pronounced decrease of the optical gap size by 0.9 eV due to the larger π-conjugated electron system compared to N-HTA 550. Structural variations or substitution patterns in N-HTAs foster the opportunity for tailoring their electronic properties.